2020
DOI: 10.5115/acb.20.136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caffeinated energy drinks on the structure of hippocampal cornu ammonis 1 and dentate gyrus of adult male albino rats

Abstract: Energy drinks are available worldwide and frequently consumed to increase energy level and compensate lack of sleep. Energy drinks consumers aim to improve their cognitive functions. Red Bull is the most popular energy drink consumed in Egypt. However, the link between the impact of energy drinks on the structure of hippocampal cornu ammonis 1 (CA1) and dentate gyrus (DG), a highly vulnerable brain regions to various insults, has not yet documented. To study the effect of energy drinks on structure of hippocam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 43 publications
3
7
1
Order By: Relevance
“…Diaz et al demonstrated in rats, substantial inflammation and oxidative stress within the hippocampus and temporal cortex following the intake of energy drinks ( 34 ). Furthermore, the ingestion of energy drinks resulted in neurodegeneration and astrocytosis in hippocampal CA1 and dentate gyrus regions of adult rats ( 29 ). However, the mechanisms whereby the energy drink consumption compromise cerebral function and integrity are presently unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diaz et al demonstrated in rats, substantial inflammation and oxidative stress within the hippocampus and temporal cortex following the intake of energy drinks ( 34 ). Furthermore, the ingestion of energy drinks resulted in neurodegeneration and astrocytosis in hippocampal CA1 and dentate gyrus regions of adult rats ( 29 ). However, the mechanisms whereby the energy drink consumption compromise cerebral function and integrity are presently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The dose of each drink ingested was determined based on similar previous studies ( 27 ) in attempt to replicate the higher level of social relevance in the context of energy drink consumption. Male mice were chosen because energy drink consumption is more popular in men than women ( 28 ), and to be consistent with previous studies ( 26 , 29 ). All groups were provided with standard rodent maintenance chow (AIN-93M, Specialty Feeds, WA, Australia).…”
Section: Methodsmentioning
confidence: 99%
“…The continuation of CA1 zone-Subiculum and is directed outward. Hippocampus has generally the three zones; polymorphic, pyramidal, and molecular (11). On the other hand, the DG formed of 3 zones: Molecular, Granular and the Hilus which is represented the Polymorphic layer.…”
Section: Introductionmentioning
confidence: 99%
“…It was documented that hippocampus, including DG, exhibits well morphological plasticity in adulthood. Few brain regions that continue their capability to form new neurons during adult life in some mammalian species (including humans) and hippocampus is one of them (11). Treatment with many agents including drugs may have associated with impairments in cognition and psychologyparticularly -the memory task -that depends on hippocampus because the adverse effect of them on Hippocampal neurogenesis (11,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation